2015
DOI: 10.1179/1476830515y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Isovaleric acid in stool correlates with human depression

Abstract: It has recently been shown that gut-derived VFAs can cross the blood-brain barrier, where isovaleric acid interferes with synaptic neurotransmitter release. The multiple correlation patterns, in addition to a potential mechanistic model, point towards a potential causal relationship between depression and isovaleric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 15 publications
4
70
2
Order By: Relevance
“…The V3 and V4 region of the 16S rRNA gene was amplified using forward primer PRK341 and reverse primer PRK806 [20], with further processing for Illumina sequencing as previously described [19]. Finally, quantification of butyric acid in cecum content was performed by GC [21]. Butyric acid was chosen as a biomarker because this is the most well-documented short-chain fatty acid to be protective against CRC [17].…”
Section: Methodsmentioning
confidence: 99%
“…The V3 and V4 region of the 16S rRNA gene was amplified using forward primer PRK341 and reverse primer PRK806 [20], with further processing for Illumina sequencing as previously described [19]. Finally, quantification of butyric acid in cecum content was performed by GC [21]. Butyric acid was chosen as a biomarker because this is the most well-documented short-chain fatty acid to be protective against CRC [17].…”
Section: Methodsmentioning
confidence: 99%
“…Szczesniak et al found that bacteria such as Faecalibacterium, Alistipes and Ruminococcus were correlated with depression, as well as the level of isovaleric acid, a type of volatile fatty acid (VFA) [112]. These associations probably occur because gut-derived VFAs can pass the BBB and further interact with synaptic neurotransmitters.…”
Section: Food and Food-derived Metabolitesmentioning
confidence: 99%
“…Regarding the gut microbiome’s influence on neurotransmitters, a recent study has shown that patients diagnosed with depression have increased volatile fatty acids such as isovaleric acid in their stool (Szczesniak, Hestad, Hanssen, & Rudi, 2015). Isovaleric acid can cross the blood-brain barrier (BBB) and affect neurotransmitter release in the CNS, thus possibly worsening this disorder.…”
Section: Biomarkers Of Interestmentioning
confidence: 99%